Effect of Ca(Ce) doping on thermopower of LaMnO3 manganites - Varshney, Dinesh; Mansuri, Irfan; Yogi, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
With a view to explain the thermoelectric effects of La0.8Ca0.2MnO3 and La0.8Ce0.2MnO3 polycrystallinesamples and to seek the role of scattering mechanism, a systematic investigation of thermopower S(T) in the metallic phase have been undertaken. Within the relaxation time approximation, it is noticed that, the phonon drag S(T) with scattering of phonons from defects, grain boundaries, phonons and charge carriers in these samples are effective in the metallic regime. Later on, Mott expression is employed to incorporate the carrier diffusive thermopower. The temperature dependence of the S(T) is determined by competition among the several operating scattering mechanisms for the heat carriers and a balance between carrier diffusion and phonon drag contributions in the polycrystalline samples of La0.8Ca0.2MnO3 and La0.8Ce0.2MnO3.